Awareness of sexually transmitted infections and cervical cancer among husbands in urban slums of Mumbai, India - Naik, D. D.; Donta, Balaiah; Iddya, Umesh; Nair, Saritha (International Journal Of Community Medicine And Public Health, 2017)
Background: Cervical cancer is the most common cancer among women, 80 percent of cervical cancer cases present with an advanced stage of the disease when cure is impossible. This may be due to lack of awareness and knowledge, lack of access to proper treatment including screening facility. Cervical cancer does not always cause symptoms during initial stage. Pap smear test helps in early diagnosis of cervical cancer and hence is successful in treatment. In recent years, there has been a growing interest in involving men into reproductive health to improve health outcomes as often husband is the leading decision maker in almost all the areas. The present paper examines the knowledge, attitude, practice and health seeking behaviour about sexually transmitted infections (STIs) and cervical cancer among husbands in a slum community of Mumbai. Methods: Baseline data from an intervention study entitled “Enhancing knowledge and promoting health seeking behaviour of couples on sexually transmitted infections and cervical cancer in urban slums of Mumbai” is used for this article. This data was collected from a random sample of 1958 husbands whose wives age was between 18-49 years, through a semi-structured interview schedule from two urban slums of Mumbai. Information was collected on socio-economic and demographic characters, awareness and symptoms of STIs and Cervical cancer, and health seeking behaviour. Results: About 76 percent husbands heard about the infections transmitted through sexual intercourse, 95.4 percent were aware of cancer whereas only 8.5 percent husbands were aware of cervical cancer and 0.3 percent were aware of Pap smear to detect the cervical cancer. About 3 percent husbands experienced at least one symptom of STIs six months prior to survey, 7.3 percent husbands reported of having sexual partner other than spouse. Most husbands were not aware of STIs symptoms specific to wives. Conclusions: There is a need for disseminating knowledge regarding STI symptoms, cervical cancer and Pap smear test for early detection of cervical cancer as well as promoting better health seeking behaviour with respect to cervical cancer and STIs. Considering sensitivity of the topic it is necessary to design separate programmes for men.